2022
DOI: 10.5114/mp.2022.123776
|View full text |Cite
|
Sign up to set email alerts
|

Directions of development of palliative care based on the literature

Abstract: Rosnące zapotrzebowanie na opiekę paliatywną oraz wyrównanie różnic w dostępie do tej formy opieki stanowią najbardziej istotne wyzwania dla współczesnego świata. Pomimo znacznego postępu jaki dokonał się w ostatnich latach w dostępie do opieki paliatywnej oraz uznania prawa człowieka do łagodzenia cierpienia za jedno z podstawowych jego praw, w wielu regionach geograficznych dostęp do leków opioidowych oraz leczenie bólu nadal są niewystarczające. W najbliższym czasie opieka paliatywna musi być przygotowana n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…It is extremely important to provide proper education as early as the medical school, as this undoubtedly influences the medical community's perception of palliative care as well as provides a foundation for effective cooperation between specialists in different fields by recognising the benefits of comprehensive care. 18 However, our study showed that independent education of primary care physicians alone is not enough. It is necessary to build a connection, to build mutual understanding and show good practices of cooperation with palliative care.…”
Section: Discussionmentioning
confidence: 58%
“…It is extremely important to provide proper education as early as the medical school, as this undoubtedly influences the medical community's perception of palliative care as well as provides a foundation for effective cooperation between specialists in different fields by recognising the benefits of comprehensive care. 18 However, our study showed that independent education of primary care physicians alone is not enough. It is necessary to build a connection, to build mutual understanding and show good practices of cooperation with palliative care.…”
Section: Discussionmentioning
confidence: 58%
“…Each year, an es-timated 56.8 million people, including 25.7 million in the last year of life, need palliative care [1]. However, the global need for palliative care will continue to grow as a result of the ageing of populations and the rising burden of chronic diseases [1,2]. Although Poland is one of the leading European countries in terms of the number of specialist palliative care services [3], access to palliative care services varies territorially and is limited in some regions [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important tasks of palliative care is to prevent and relieve suffering through the early identification, correct assessment and treatment of pain and other problems, such as physical, psychosocial or spiritual [1]. Palliative care providers must be prepared for the next challenges related to providing patients with individualized care adapted to the stage of the disease and reported symptoms and social, cultural and religious conditions [2]. Active participation in providing care to patients with chronic conditions is considered stressful and burdensome and could result in the incidence of symptoms of burden in caregivers' functioning [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hospice and Palliative Care Evaluation Symptoms and Problems Checklist (HOPE-SP-CL): a simple tool in the eligibility process for patients in palliative and hospice care Dear Editor, discussions about the optimal model for qualifying patients for palliative and hospice care continue [1]. The present legal system in Poland only defines the general organisational framework for this process.…”
mentioning
confidence: 99%
“…Therefore, it is worth considering the introduction of this tool to national settings. Szanowny Panie Redaktorze, nie milkną dyskusje dotyczące optymalnego modelu kwalifikowania pacjentów do opieki paliatywnej i hospicyjnej (OPH) [1]. Aktualny system prawny w Polsce określa jedynie ogólne ramy organizacyjne tego procesu.…”
unclassified